Changes in Spectral Power and Functional Connectivity of Response-Conflict Task After Neurofeedback Training - Rab Nawaz; Humaira Nisar; Yap Vooi Voon (IEEE Access, 2020)
Neurofeedback training (NFT) teaches self-control of brain activity to the subjects by measuring brain waves and providing a feedback signal in real time. NFT is considered to be a promising tool for healthy people to enhance cognition, however its specific effects on response-conflict are unknown. This study employed 50 healthy participants into two groups (NFT group = 25, control group = 25), in order to explore the NFT effects towards response-conflict resolution phenomenon. Changes in Absolute power and functional connectivity in different bands of response-conflict EEG, were investigated. The EEG of each participant was recorded while performing a response-conflict task before and after NFT. The results show an increase in theta and alpha band powers and functional connectivity. No training specific modulation is observed in beta band functional connectivity. A significant improvement in theta and alpha band functional connectivity is observed in the NFT group that is not present in the control group. These findings provide a strong rationale for the use of NFT in the resolution of response-conflict phenomenon in healthy human beings.